Museum Experience and Reasoning about Evolution: A Case Study of Educated Indonesians - Setioko, Wahyu (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
This qualitative case study investigates the impact of informal learning experiences at a natural history museum on individuals' reasoning about evolution. Four Indonesian participants, aged 25-30, were interviewed about their understanding of evolutionary concepts after engaging in free-choice museum visits, while two did not visit the museum. Interviews were analyzed using a coding scheme to identify three reasoning patterns: Informed Naturalistic Reasoning (INR), Novice Naturalistic Reasoning (NNR), and Creationist Reasoning (CR). Findings reveal that museum-goers predominantly employed INR, demonstrating a clearer understanding of evolutionary concepts through gene mutation and inheritance, while non-museum-goers frequently used NNR and CR, reflecting intuitive and religious perspectives. The study highlights the museum's role in facilitating scientific understanding and suggests that informal learning environments can effectively complement formal education in fostering scientific literacy.